Analisis Pengaruh Literasi Keuangan dan Teknologi Media Sosial Terhadap Minat Berinvestasi Pada Mahasiswa Jurusan Manajemen Universitas Pattimura - Merci Souisa; Lilian Loppies; Restia Christany (Jurnal Minfo Polgan, 2023)
This study aims to determine the effect of financial literacy and social media technology on the interest in investing in Students majoring in Management from Pattimura University, Ambon. It is important for students to have knowledge about financial literacy because it can lead to welfare for their future life, along with the major growth of social media technology, student are able to search a lot of information about investment, the information are about how to invest and what company stock are worth to buy to gain a profit in short or long term of investment. The technology also make it more easier for student to make an investment. Interest in investing are passion, trend or encouragement to invest in one or more assets at this time and expect for profit at future time. Quantitative descriptive is the type of research used in this study with the population are students majoring in financial management at Pattimura University Ambon class of 2017-2019 who had completed the Investment Management and Portfolio Theory course. The sampling technique used a questionnaire with a five-point Likert scale. The analysis technique used is multiple linear regression analysis. The results of this study find that both of the hypothesis are accepted. Financial literacy have a positive and significant effect on the interest in investing and social media technology also have a positive and significant effect on the interest in investing in students majoring in financial Management at Pattimura University, Ambon.